An Integrated TAM–TPB Model for Gen Z Muslims' Purchasing of Halal Products on Social Commerce Platforms - Rahmawaty, Anita; Saputri, Dilla Ajeng Diah (Asian Journal of Management Analytics, 2025)
This study aims to develop a model of halal product purchasing behavior on social commerce platforms by integrating the TAM (Technology Acceptance Model) and TPB (Theory of Planned Behavior) models, as well as additional variables of halal lifestyle and privacy awareness. Data were collected from 450 Gen Z Muslim respondents in Central Java, Indonesia, and analyzed using PLS-SEM, a technique effective in evaluating construct validity, reliability, and inter-variable relationships. The results indicate that perceived usefulness and privacy awareness significantly influence attitudes toward purchasing halal products, while perceived ease of use does not have a significant effect. The TPB factors (attitude, subjective norm, and perceived behavioral control) together with privacy awareness were found to form strong behavioral intention. Conversely, halal lifestyle does not significantly influence behavioral intention. However, halal lifestyle, perceived behavioral control, and behavioral intention significantly contribute to explaining halal product purchase behavior. These findings suggest that social commerce platforms should strengthen features supporting halal lifestyles and enhance app usability as strategies to deepen consumer engagement and strengthen business performance in the halal market.